Development of Problem-Based Learning-Based Independent Curriculum LKPD to Improve Students' HOTS - Asmana, Arezqi Tunggal; Rohim, Abdur; Aini, Khafidhoh Nurul; Winata, Vina Pandu (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
This research is a development research that aims to develop Problem Based Learning Independent Curriculum Worksheets (LKPD) on Trigonometry material that are valid, practical, and effective to improve students' Higher Order Thinking Skills (HOTS). The LKPD developed is part of the teaching module of the Independent Curriculum. This study uses the 4D development model, which consists of the Defining, Designing, Developing, and Deployment stages. However, the Deployment stage is not carried out. The trial was carried out on Class X students of SMA Negeri 1 Sekaran, Lamongan City. The analysis techniques used in this study were grouped into three, namely analysis of LKPD validity data, analysis of LKPD practicality data, and analysis of LKPD effectiveness data. The results showed that the LKPD Independent Curriculum based on Problem Based Learning on Trigonometry material that was developed met the valid, practical, and effective categories to improve students' HOTS. Validity is shown by the average percentage of LKPD validation results is 91%. Practicality is indicated by (1) the average percentage of LKPD implementation is 92%, (2) the percentage of teacher responses is 94%, and (3) the percentage of student responses is 88%. Effectiveness is shown by (1) the average percentage of student activity is 87% and (2) the HOTS increase of students from written assessments is 96%.